Natural Products with Skin – Whitening Effects - JEN-WEN LIN (2007)
UV radiation is widely considered as a major cause of skin pigmentation. Upon exposure to UV radiation, the melanocytes increase the production of intracellular nitric oxide, which triggers signal transduction cascades to initiate melanogenesis by tyrosinase. UV radiation also influences melanogenesis through a paracrine regulation process involving the keratinocytes. Although a number of hypopigmenting products have been developed, those from natural sources are preferred and will predominate in the cosmetics market. More active compounds such as phenols, flavonoids, coumarins and other derivatives have been identified from natural sources. This article summarized natural skin whitening products involving tyrosinase blockers like phenols and polyphenols, and non-tyrosinase blockers like α-MSH, melanosome transferase and cytokine inhibitors. In addition, the skin-whitening effects and the mechanisms of these natural products were also reviewed. Most of the compounds achieve the hypopigmenting effect by inhibiting tyrosinase; however, some interesting compounds blocking the upstream regulation points of melanogenesis are extraordinarily promising for developing novel whitening agents.